Acacia Polyphenol Ameliorates Atopic Dermatitis in Trimellitic Anhydride-Induced Model Mice via Changes in the Gut Microbiota - Nobutomo Ikarashi; Natsumi Fujitate; Takumi Togashi; Naoya Takayama; Natsuko Fukuda; Risako Kon; Hiroyasu Sakai; Junzo Kamei; Kiyoshi Sugiyama (Foods, 2020)
We have previously shown that acacia polyphenol (AP), which was extracted from the bark of Acacia mearnsii De Wild, exerts antiobesity, antidiabetic, and antihypertensive effects. In this study, we examined the effect of AP on atopic dermatitis. Trimellitic anhydride (TMA) was applied to the ears of mice to create model mice with atopic dermatitis. The frequency of scratching behavior in the TMA-treated group was significantly higher than that in the control group, and the expression levels of inflammatory markers (tumor necrosis factor-α, interleukin-6, inducible nitric oxide synthase, and cyclooxygenase-2) in the skin also increased. In contrast, both the frequency of scratching behavior and the expression levels of skin inflammatory markers in the AP-treated group were significantly lower than those in the TMA-treated group. The abundances of beneficial bacteria, such as Bifidobacterium spp. and Lactobacillus spp., increased in the AP-treated group compared with the TMA-treated group. Furthermore, the abundances of Bacteroides fragilis and Clostridium coccoides in the gut, which are known for anti-inflammatory properties, increased significantly with AP administration. The present results revealed that AP inhibits TMA-induced atopic dermatitis-like symptoms. In addition, the results also suggested that this effect may be associated with the mechanism of gut microbiota improvement.